Development of welding technique teaching module based on augmented reality ıntegrated (ARI) equipped with 3D animation simulation to ımprove 21st century skills of vocational high school students - Yunus; Djoko Suwito; Aries Dwi Indriyanti; Rizdana Galih Pambudi; Dyah Permata Sari (Cogent Education)
21st-century skills are critical abilities for today’s generation to face changes and challenges in this era. The industrial world greatly needs competence in the field of welding. This study comprehensively seeks to develop a technology-enhanced teaching module using augmented reality integrated (ARI) and animation for valid, effective, and practical learning. This development research was conducted following the DBR model, which consists of five stages: analysis, design, development, implementation, and evaluation. Qualitative data were obtained through comments and suggestions for improvement in questionnaires and interviews. Quantitative data were obtained from validation test scores, practicality tests, validity and reliability tests of questions, and pretest and posttest score data. Data were analyzed using percentage analysis and qualitative descriptions. The validation results from experts obtained a value of 91% with valid criteria. The practicality of the module obtained a value with an average of 84% with practical criteria. The effectiveness of the ARI teaching module was calculated using the N-Gain formula, producing an average value of 0.36, which meets moderate criteria. It can be concluded that the ARI teaching module produced is valid, effective, and practical for training students’ 21st-century skills.